P82 Educational innovation pilot of a simulated scenario. (3rd November 2019) - Foster, Gail; Bush, Emma; Crawford, Amanda
Abstract : Introduction: Rationale and current simulation practice -. Simulation based activities are used to support learning as simulation provides students with a safe environment in which to practice skills (Morrell-Scott, 2018). Current simulated practice at the University of Hull has involved stand alone clinical skills sessions, covering one aspect of practice. A new clinical simulation suite (Allam Medical Building) prompted lecturers to review simulated teaching activities and to recognise simulated practice within the adult nursing programme could be improved. Aims of the simulation: Demonstrate problem solving skills. Demonstrate prioritisation/delegation skills. Demonstrate communication skills. Demonstrate basic life support skills, in accordance with Resuscitation Council (UK) in hospital resuscitation guidance (2015). Description: Scenario - An orthopaedic ward scenario, including cardiac arrest, was piloted with second year BSc Pre-registration Adult Nursing students. Students' were grouped and randomly allocated to roles. The aims, expectations and purpose of the scenario were shared with students. Students allocated to staff nurse and student nurse roles had a handover with the activity facilitator who assumed the role of ward sister/charge nurse. A second facilitator observed the scenario and instigated the cardiac arrest activity. Summary of outcomes: Debrief -took place at the end of the scenario. Feedback from students and facilitators was positive. Students felt the scenario was realistic and reflected practice. Students felt challenged when assuming staff nurse and student roles. Students felt the cardiac arrest activity provided a degree of realism often lacking when undertaking basic life support with mannequins on the floor. Discussion, conclusion and recommendations: Facilitators felt students engaged well with the activity, demonstrating effective verbal and non-verbal communication skills. Some students demonstrated effective prioritisation and delegation skills. However, other students were less effective at prioritising and delegating. This was discussed during the debrief. Students recognised the value of this activity in supporting their confidence to respond to cardiac arrests in hospitals. Students recognised the importance of prioritisation and delegation in practice. Students requested the inclusion of more simulated activities such as this in their programme. Recommendations: Develop stage specific simulated scenarios. Involve students and practice partners in design of scenarios. Improve scenario structure with rotation of roles and mini debriefs. Feedback: 'Reflects practice' 'Really good cardiac arrest scenario' 'Realistic as there were different demands' 'Good activity for allowing students to make decisions' References: Morrell-Scott, N. (2018) Confidence and deeper learning: simulated practice within pre-registration nurse education. British Journal of Nursing, Vol 27, No 14. Resuscitation Council (UK) (2015) in hospital resuscitation guidance. London: Resuscitation Council (UK). Available https://www.resus.org.uk [Accessed 15/03/2019]